Long-term health-related quality of life improvements among patients treated with lurasidone: results from the open-label extension of a switch trial in schizophrenia. Issue 1 (December 2016) - Awad, George; Ng-Mak, Daisy; Rajagopalan, Krithika; Hsu, Jay; Pikalov, Andrei; Loebel, Antony
Abstract Background Long-term improvement of health-related quality of life (HRQoL) in schizophrenia may improve adherence and reduce relapse and rehospitalization. This analysis examines long-term changes in HRQoL among patients with schizophrenia switched to lurasidone from other antipsychotics. Methods Patients who completed an open-label 6-week switch study continued on lurasidone for an additional 24-weeks. HRQoL was measured using the self-reported Personal Evaluation of Transitions in Treatment (PETiT) scale and Short-Form 12 (SF-12) questionnaire. The PETiT assessed HRQoL via total and domain scores (adherence-related attitude and psychosocial functioning). The SF-12 assessed patients' mental and physical component summary scores (MCS and PCS). Mean changes from the initial baseline were calculated at extension baseline and extension endpoint using analysis of covariance models. Analyses were further stratified by prior antipsychotic medication and responder status; responders were defined as having a ≥20 % improvement in Positive and Negative Syndrome Scale during the first 6-weeks of treatment. Results The analysis included 144 patients with PETIT or SF-12 data who received ≥1 dose of lurasidone. Mean (standard deviation) PETiT total score improved significantly from 34.9 (9.3) at baseline to 39.5 (8.9) at extension baseline and 39.1 (9.0) at extension endpoint, representing improvements of 4.5 (7.9) and 5.1 (7.2) points, respectively (bothp < 0.001). Significant improvements in adherence-related attitude and psychosocial functioning were observed at extension baseline and extension endpoint (allp < 0.001). Improvement in SF-12 MCS score was observed at extension baseline and endpoint, and PCS score at extension endpoint (allp < 0.01). Patients who switched from quetiapine and aripiprazole showed significant improvement of PETiT total score and adherence-related attitude at extension baseline and extension endpoint. In addition, patients who switched from quetiapine, risperidone, aripiprazole, or ziprasidone showed significant improvement in MCS scores from baseline to extension endpoint. Responders to lurasidone demonstrated greater improvement in PETiT total, psychosocial functioning, and MCS scores at extension baseline than nonresponders. Conclusions After switching to lurasidone, patients with schizophrenia experienced HRQoL improvements that were sustained for an additional 24 weeks of treatment. Further study is warranted to understand the implications of these improvements in terms of employment, adherence, relapse, and rehospitalization. Trial registration Clinical trials.gov identifierNCT01143090 (June 10th, 2010).